Animation 1 : learn to animate step by step - Blair, Preston (Irvine, CA : Walter Foster Publishing, 2019)
"... covers the most important aspects of cartooning, such as working out layouts, planning scenes, and synchronizing mouth action. It also provides instruction on drawing a variety of believable animated characters, with tips on using lines of action to create realistic motion." --back cover
"Constructing the head -- Using 'squash' and 'stretch' -- Creating expressions -- Drawing action cycles." --front cover
Title from cover
1 10
Keywords: Animation (Cinematography) -- Technique; Caricatures and cartoons; Cartooning -- Technique